Regulation (EC) No 1901/2006 on medicinal products for paediatric use & clinical research in vulnerable populations - Lehmann Birka (BMC, 2008)
Abstract Before any medicinal product is authorised for use in adults, it must undergo extensive pharmaceutical consistency and stability tests, toxicological tests and clinical trials to ensure that it is of high quality, safe and effective. The same approach may not always be applied to medicinal products used to treat children. Studies showed that over 50% of the medicinal products used in children may not have been tested for use in this age group. The absence of suitable authorised medicinal products to treat conditions in children results from the fact that pharmaceutical companies do not adapt medicinal products to the needs of the paediatric population. This leaves health care professionals with no alternative other than to use medicinal products "off-label" and to use unauthorised products with the associated risks of inefficacy and/or adverse reactions. The Regulation (EC) No 1901/2006 sets up a system of requirements, rewards and incentives, together with horizontal measures, to ensure that medicinal products are researched, developed and authorised to meet the therapeutic needs of children. The Regulation is addressed to: 1. The pharmaceutical industry by setting out the legal framework for receiving rewards and incentives by conducting clinical trials in the paediatric population. 2. The Member States to set out to support research into, and the development and availability of, medicinal products for paediatric use. 3. The Community as funds for research into medicinal products for the paediatric population shall be provided for in the Community budget in order to support studies relating to medicinal products or active substances not covered by a patent or a supplementary protection certificate. The legal framework for conducting clinical trials, including children/minors, is set up in Directive 2001/20/EC, the Clinical Trials Directive (CTD), for the European Union (EU). The CTD establishes specific provisions regarding conduct of clinical trials, including multi-centre trials, on human subjects involving medicinal products and in particular relating to the implementation of good clinical practice. Compliance with this good practice provides assurance that the rights, safety and well-being of trial subjects are protected, and that the results of the clinical trials are credible. The CTD is addressed to all investigators conducting clinical trials including clinical trials in the paediatric population and had to be applied accordingly. In the framework of the authorisation of medicinal products regulated by the Regulation (EC) No 726/2004 and Directive 2001/83/EC as amended and the CTD, and additional implementing Directives and guidelines, the new Regulation (EC) No 1901/2006 is an important new piece of legislation focusing on the requirements to improve the situation for the paediatric population. All Regulations/Directives to be found: http://ec.europa.eu/enterprise/pharmaceuticals/eudralex/vol1_en.htm